Use of Carrageenan in Pharmaceutical Technology [Karragenin Farmasotik Teknolojideki kullanimi] - (:unkn) unknown (My University, 1999)
Use of Carrageenan in Pharmaceutical Technology Carrageenan is a natural polymer obtained from various seaweeds and is being used in pharmaceutical formulation studies increasingly. There are three types of carrageenan iota, kappa and lambda. Other probable types of carrageenan are mu, nu, xi and theta. In this paper, the physical, chemical and pharmacological properties of carrageenan are given. There is also information about its application in different areas, especially in pharmaceutical technology.
Keywords: Carrageenan; Hydrogel; Natural polymer